2018
DOI: 10.4317/jced.54561
|View full text |Cite
|
Sign up to set email alerts
|

Decayed, missing, and restored teeth in patients with Neurofibromatosis Type 1

Abstract: BackgroundNF1 is a relatively frequently occurring autosomal dominant inherited disease. There are conflicting reports about oral health status in NF1. The aim of this study was to analyze the dental status of patients with neurofibromatosis type 1 (NF1).Material and MethodsRadiographs of 179 patients with NF1 were analyzed for decayed, missing, and filled teeth (DMFT) in a cross-sectional, retrospective study. The results were compared to age- and sex-matched controls of individuals not affected by NF1. The N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…The results suggest that NF1 as such does not cause susceptibility to caries (Table 1 ). A strict professional caries prevention is advised because gingival enlargements and motoric clumsiness may hamper the maintaining patient’s oral health and our results in agreement with recently published study of Friedrich et al [ 41 ].…”
Section: Resultssupporting
confidence: 92%
“…The results suggest that NF1 as such does not cause susceptibility to caries (Table 1 ). A strict professional caries prevention is advised because gingival enlargements and motoric clumsiness may hamper the maintaining patient’s oral health and our results in agreement with recently published study of Friedrich et al [ 41 ].…”
Section: Resultssupporting
confidence: 92%
“…Freidrich and Reul showed lowest DMFT index in NF1 group when compared with reference group solely in mandibular nerve region. They reported missing teeth were more frequently registered with NF1 group 14 . In present case localized severe attachment loss and bone loss was seen with mandibular region when compared with maxillary region thus showing a predilection towards mandibular tooth loss.…”
Section: Discussionmentioning
confidence: 96%
“…Although a case of gingival neurofibroma in the attached gingiva has been reported [ 30 , 31 ], so far there is a lack of evidence regarding whether NF1 patients may present periodontal disease without tumors directly involving the oral cavity. In our study, as all NF1 patients did not have neurofibromas in the maxilla or mandible, our findings for the first time demonstrated that NF1 patients were at a high risk of periodontitis.…”
Section: Discussionmentioning
confidence: 99%